The Use of a Jet Column with Different Nozzles as a Reactor for Biodiesel Reaction with Crude Palm Oil as Feedstock - Dijan Supramono (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Biodiesel may be produced by trans-esterification reaction of vegetable oil, which transforms triglycerides into alkyl esters as biodiesel and glycerol as a byproduct, in the presence of an alcohol reactant and a acid or base catalyst. The major obstacle of preventing biodiesel commercialisation is low mass transfer rates from methanol into oil phase to achieve high yield due to large difference in fluid viscosities, i.e. low viscosity methanol and high viscosity oil. Many techniques have been proposed to overcome this obstacle, most of which involve high mole ratio of methanol to triglycerides exceeding 6, but none of them utilised fluid mechanic techniques to fix up the obstacle. The present research adopts a finding in fluid mechanic field that notched and tabbed nozzles are capable of intensifying shear stress between 2 different flows, which consequently increases the contact areas of the flows considerably. For this purpose, in the present research, a jet column was utilised as a reactor where the mixture of reactants, i.e. crude palm oil (CPO) and methanol with catalyst NaOH were recirculated and injected downward vertically into the reactor column from a nozzle at the top of reactor. The type of nozzles and the mole ratio of methanol to CPO were varied (3.75:1; 4.5:1; 5.25:1 and 6:1) to investigate their effects on yield and conversion of the reaction conducted for 60 minutes at temperatures 53-58oC. Nozzles used were notched, tabbed and conventional circular nozzles for comparison. The highest conversion and yield of biodiesel were achieved at mole ratio 6:1 attaining respectively 87.2% and 96.8% using notched nozzle, 87.8% and 96.6% using tabbed nozzle and 71.2% and 75.1 % using circular nozzle for comparison. Therefore, using notched and tabbed nozzles can reduce the excess of methanol reactant thus saving its separation cost while producing high yield of biodiesel.